HOW TO INCREASE THE BEGINNING SPEED OF MINERAL FERTILIZERS DISCONTINUED FROM THE DISK AND ITS TECHNICAL SOLUTION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The object of research is the process of increasing the initial rate of removal of mineral fertilizers from the pneumomechanical apparatus for even application. The centrifugal pneumatic-mechanical device is designed to increase the initial speed by simultaneously throwing two functions, the first - the release of mineral fertilizers, the second - the creation of additional air flow and directing it behind the thrown fertilizer grains. A pneumatic-mechanical device, extracted from the proposed center, ensures even spreading of fertilizers on the field with components of different sizes, shapes and densities.